Hints for the busy housewife (London : Health & Cleanliness Council)
1939-05 1939 1930s 50 pages : illustrations HINTS FOR THE BUSY HOUSEWIFE SECTION I HOUSEHOLD CLEANING "CHILDREN never forget the lessons of a clean home" — the observance of cleanliness in the home is the very best way of leading them to form cleanly habits. Moreover, clean home surroundings are essential to the good health of the family. Therefore scour out the corners — they harbour the dust and the germs. Wash and clean floors whenever possible — a home cannot be too spotless for health. It is false economy not to have a lamp in the dark corners of the home. “Where there is darkness there is dirt and danger,” for it is on that ill-lighted staircase or in that dark room and passage that accidents occur and dust accumulates. Often the lack of sufficient lighting causes waste of time. It is a very real advantage to have a good light that can be switched on in the kitchen, the store cupboard, the linen cupboard, the larder, etc. The light in the kitchen, which some people are apt to think unimportant, should not be too small, and clear glass lamps should not be used — pearl or opal lamps give a light which is restful and not glaring to the eyes. The following is a suggested routine for the weekly cleaning of rooms in an average-sized house where work is done by the mistress or a maid: Page Three 177/5/8/1